2020
DOI: 10.1038/s41598-020-68041-y
|View full text |Cite
|
Sign up to set email alerts
|

Free l-glutamate-induced modulation in oxidative and neurochemical profile contributes to enhancement in locomotor and memory performance in male rats

Abstract: Glutamate (Glu), the key excitatory neurotransmitter in the central nervous system, is considered essential for brain functioning and has a vital role in learning and memory formation. earlier it was considered as a harmful agent but later found to be useful for many body functions. However, studies regarding the effects of free l-Glu administration on CNS function are limited. Therefore, current experiment is aimed to monitor the neurobiological effects of free l-Glu in male rats. l-Glu was orally administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 61 publications
2
9
0
1
Order By: Relevance
“…Our previous studies with oxaliplatin demonstrate that platinum‐based anti‐cancer agents induce oxidative stress leading to neuronal damage and death underlying post‐treatment dysfunctions 7 . MSG‐induced neuroprotection may be due to improvements in the endogenous antioxidant profile, with reduction of lipid peroxidation (malondialdehyde, MDA) and in glutation (GSH) levels 56 , and probably to an indirect effect on microtubules after interaction with a receptor found only on neural cells 55 . Further studies are warranted to determine the pathways, receptors and mediators involved in the neuroprotective effects of MSG, including the possibility that it might prevent platinum accumulation (another mechanism underlying long‐term peripheral sensory neuropathy 57,58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies with oxaliplatin demonstrate that platinum‐based anti‐cancer agents induce oxidative stress leading to neuronal damage and death underlying post‐treatment dysfunctions 7 . MSG‐induced neuroprotection may be due to improvements in the endogenous antioxidant profile, with reduction of lipid peroxidation (malondialdehyde, MDA) and in glutation (GSH) levels 56 , and probably to an indirect effect on microtubules after interaction with a receptor found only on neural cells 55 . Further studies are warranted to determine the pathways, receptors and mediators involved in the neuroprotective effects of MSG, including the possibility that it might prevent platinum accumulation (another mechanism underlying long‐term peripheral sensory neuropathy 57,58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that impaired glutamate signaling is associated with cognitive dysfunction [ 56 ]. Additionally, chronic supplementation of glutamate at adequate amounts can improve memory performance, including spatial, recognition, and associative memory processes [ 64 ]. Interestingly, in the present study, ULK1, a serine/threonine-protein kinase, was the only protein expressed uniquely in diabetic mice treated with cordycepin ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…GABA is an essential amino acid that serves as an inhibitory neurotransmitter for brain and plays role in information processing, neuronal development and cognition. Studies are suggesting that aggregation of Aβ peptides in the hippocampus interfere with GABA inhibitory interneuron function and promote memory impairment [5]. Further, defects in the cholinergic system can reduce the ACh levels in the brain due to the loss of cholinergic neurons and neurotransfomation.…”
Section: Introductionmentioning
confidence: 99%